Research of the system of professional development of personnel in non-profit organizations of the Stavropol krai - G. S. Shelkoplyasova; A. O. Gazimagomedova; O. A. Cichova (Вестник Северо-Кавказского федерального университета, 2023)
Introduction. The article analyzes the system of professional training and personnel development by the example of non-profit organizations. Today, for the non-profit sector, the issues of improving human resources (professional development and retraining of personnel) are the most pressing. The purpose is to analyze the system of professional development of personnel of non–profit organizations of Stavropol and give an assessment. Materials and methods. The research is based on the use of general scientific special methods: abstract-logical, economic-statistical and systematic. Results and discussion. The goal of non-profit organizations is to improve the welfare of civil society, create and maintain favorable conditions for its development. The professional development of NPO personnel in the Stavropol Krai is a positive trend. Areas of personnel development in the non-profit sector are developing quite actively, which in turn has a positive effect on the professionalism of personnel and the quality of the tasks they perform. The implementation of professional development programs involves the use of a large number of methods and forms of training and personnel development, and the number of training sites increases every year. As part of the study, the problems that received the largest number of votes among respondents were identified: low level of information openness of NGOs in the region; lack of methodological support for solving specific problems; insufficient development of the development potential of the third sector. Despite the fact that today the region cannot be called a leader in the regional rating of non-profit organizations, compared to the previous year, there has been a significant increase in the rating indicator. Conclusion. An analysis of the available data on the results of the implementation of training events and programs allowed us to draw a conclusion about the level of work of government authorities and representatives of the non-profit sector in the region.